A Framework of Brand Management to Build Business Strategies as a Function of Market - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Shankar, K. (Opción, 2019)
TIn the market how a brand is perceived the planning and analysis in mar- keting is known as brand management. For brand management with the tar- get market develop a good relationship is very necessary. The product itself include in tangible elements like packaging, price and looks in brand man- agement. The relationships with the brand and experiences that the consum- ers share are known as the intangible elements. Relationship with members of the supply chain and all aspects of the brand association of consumer are analyzed by a brand manager.